2015
DOI: 10.1016/j.jmps.2015.05.008
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical consideration of the ballistic response of continuous graphene membranes

Abstract: The remarkable properties of graphene, including unusually high mechanical strength and stiffness, have been well-documented. In this paper, we combine an analytical solution for ballistic impact into a thin isotropic membrane, with ab initio density functional theory calculations for graphene under uniaxial tension, to predict the penetration resistance of multilayer graphene membranes. The calculations show that continuous graphene membranes could enable ballistic barriers of extraordinary performance, enabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 42 publications
0
32
0
Order By: Relevance
“…This exceptional behavior was attributed to the superior in-plane speed of sound, high strength, stiffness, and structural anisotropy of multilayer graphene. A recent theoretical study (Wetzel et al 2015) on the ballistic response of continuous graphene membranes showed that ideal pristine graphene exhibits 10-100 stronger resistance to penetration per unit mass than conventional barrier materials, indicating an enormous potential of graphene-based armor materials.…”
Section: With Permissionmentioning
confidence: 99%
“…This exceptional behavior was attributed to the superior in-plane speed of sound, high strength, stiffness, and structural anisotropy of multilayer graphene. A recent theoretical study (Wetzel et al 2015) on the ballistic response of continuous graphene membranes showed that ideal pristine graphene exhibits 10-100 stronger resistance to penetration per unit mass than conventional barrier materials, indicating an enormous potential of graphene-based armor materials.…”
Section: With Permissionmentioning
confidence: 99%
“…(4), . Both experimental (Lee et al, 2008) and computational (Wetzel et al, 2015) studies have shown that the nonlinear elastic behavior of 2D crystals under axial tension can be described by 2 2 + 2 2…”
Section: Simulations Of Nano-projectile Impact On H-bn Monolayer and mentioning
confidence: 99%
“…By Ref. (Wetzel et al, 2015), using the scaling factor of h-BN divided by that of graphene, the ballistic limit of h-BN is predicted as 0.86 that of graphene , approximately 10 times that of Kevlar 129 (V bl-graphene ~ 11.6×V bl-Kevlar in (Wetzel et al, 2015)). From Table 3, we found that h-BN membrane, similarly to graphene, is an excellent light-weight armor material due to its low density, high strength, superior in-plane wave speed and the remarkable ballistic limit.…”
Section: Ballistic Limit Of Monolayer H-bnmentioning
confidence: 99%
See 1 more Smart Citation
“…By varying nanoparticle size and energy, the mechanical properties of suspended graphene under bombardment were explored at energies where nanoparticle deformation [1], fracture toughness [2], and elastic modulus [3], among other properties, result in varying interactions. These experiments help to better elucidate the potential role of graphene in ballistics applications [4] as well as the utilization of nanoparticle bombardment to modify graphene membranes for a variety of applications such as filtration and separation at the nanoscale with high permeances [5].In this study, we utilize a custom nanoparticle generation system, an Ionwerks NPlanter, to bombard suspended graphene produced by CVD with silver nanoparticles at supersonic velocities and, in some instances, at hypervelocitiy. The instrument has the capability to size select nanoparticles at specified diameters <30 nm and accelerate them at suspended graphene with energies up to 30 keV with controlled fluence.…”
mentioning
confidence: 99%